Urban Functional Specialisation and the Interplay between Firm's Communication Costs - Giuseppe Francesco Gori (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This paper focuses on the functional specialisation of a system of cities, with particular attention to the role and the formation process of secondary business centers. At the European level, the latters can be identified in the large number of regional capitals, and properly defined as cities hosting both headquarters of multi-location firms and providers of standard non-tradable business services (SBS). I present a theoretical model in which the changes in urban system's degree of functional specialisation are linked to (i) firms' organisational choices, since firms decide whether splitting into headquarter and production plant or remaining integrated in a single establishment and to (ii) firms' location decision with regards to the proximity with the tradable advanced business services providers. I model two types of communication costs, one between headquarters and advanced tradable business services providers (ABS) and one between headquarters and production plants. The interplay between the two types of communication costs is shown to have effects on the transition process from an "integrated" urban system where each city hosts every different functions to a "functionally specialised" urban system where each city is either a primary business center (hosting ABS), a secondary business centers (SBS) or a pure manufacturing city and all this city-types coexist in equilibrium. In particular, I find that maximum functional specialisation of the urban system turns out to be feasible only if firms face a very high share of the total costs represented by their heaquarter spending.
Keywords: R30; L23; R12; 330